The colorectal surgeon's personality may influence the rectal anastomotic decision. (5th July 2018) - Moug, S. J.; Henderson, N.; Tiernan, J.; Bisset, C. N.; Ferguson, E.; Harji, D.; Maxwell‐Armstrong, C.; MacDermid, E.; Acheson, A. G.; Steele, R. J. C.; Fearnhead, N. S.; ,
Abstract: Aim: Colorectal surgeons regularly make the decision to anastomose, defunction or form an end colostomy when performing rectal surgery. This study aimed to define personality traits of colorectal surgeons and explore any influence of such traits on the decision to perform a rectal anastomosis. Method: Fifty attendees of The Association of Coloproctology of Great Britain and Ireland 2016 Conference participated. After written consent, all underwent personality testing: alexithymia (inability to understand emotions), type of thinking process (intuitive versus rational) and personality traits (extraversion, agreeableness, openness, emotional stability, conscientiousness). Questions were answered regarding anastomotic decisions in various clinical scenarios and results analysed to reveal any influence of the surgeon's personality on anastomotic decision. Results: Participants were: male (86%), consultants (84%) and based in England (68%). Alexithymia was low (4%) with 81% displaying intuitive thinking (reflex, fast). Participants scored higher in emotional stability (ability to remain calm) and conscientiousness (organized, methodical) compared with population norms. Personality traits influenced the next anastomotic decision if: surgeons had recently received criticism at a departmental audit meeting; were operating with an anaesthetist that was not their regular one; or there had been no anastomotic leaks in their patients for over 1 year. Conclusion: Colorectal surgeons have speciality relevant personalities that potentially influence the important decision to anastomose and could explain the variation in surgical practice across the UK. Future work should explore these findings in other countries and any link of personality traits to patient‐related outcomes.